Acute Urinary Retention in the Male Child from Urethral Calculi: A Report of Three Cases - L. O. Mbouché; G. Ondobo Andzé; A. S. Nwaha Makon; D. Nyanit Bob; E. Njuma Tamufor; A. L. Amenglé; F. F. Mouafo Tambo; P. Y. Mure; J. Zé Mikandé; F. F. Angwafo (Case Reports in Urology)
Urinary stones are uncommon in children. Urethral location of calculi can give rise to various clinical manifestations. We report three cases of urethral lithiasis presenting with acute urinary retention in children.